2021
DOI: 10.1097/md.0000000000025719
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid therapy for COVID-19

Abstract: Background: Corticosteroid treatment is an effective and common therapeutic strategy for various inflammatory lung pathologies and may be an effective treatment for coronavirus disease 2019 (COVID-19). The purpose of this systematic review and meta-analysis of current literature was to investigate the clinical outcomes associated with corticosteroid treatment of COVID-19. Methods: We systematically searched PubMed, medRxiv, Web of Science, and Scopus databases through M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Hence, it was not considered in further studies [ 54 , 55 , 56 , 57 ]. Deflazacort, a corticosteroid, was left out, as several corticosteroids are already in clinical trials and are being used clinically due to their anti-inflammatory properties in treating COVID-19 complications [ 58 , 59 ]. Cefaclor and other cephalosporin antibiotics were strongly considered but ultimately not included.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was not considered in further studies [ 54 , 55 , 56 , 57 ]. Deflazacort, a corticosteroid, was left out, as several corticosteroids are already in clinical trials and are being used clinically due to their anti-inflammatory properties in treating COVID-19 complications [ 58 , 59 ]. Cefaclor and other cephalosporin antibiotics were strongly considered but ultimately not included.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was not considered further studies [45][46][47][48]. Deflazacort, a corticosteroid, was left out, as several corticosteroids are already in clinical trials and are being used clinically due to their anti-inflammatory properties in treating COVID-19 complications [49,50]. Cefaclor and other cephalosporin antibiotics were strongly considered but ultimately not included.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that corticosteroids have a good anti-inflammatory effect. Studies have shown that corticosteroids therapy can also improve the mechanical ventilation of severe COVID-19 patients and has lower mortality than patients with routine nursing [112]. In short, there are still many clinical studies related to antiviral therapy.…”
Section: Antiviral Therapymentioning
confidence: 99%